The consequences costs of drug trafficking: a case on sahabat’s clients / Sharifah Fadzlon Abdul Hamid …[et al.] - Abdul Hamid, Sharifah Fadzlon; Omar, Normah; Sulaiman, Suzana; Wee, Shu Hui (Universiti Teknologi MARA Cawangan Selangor, 2014)
Drug trafﬁcking, a type of money laundering is the most serious organized crime problem in the world today with drug users as the ﬁnancier for the organized crime through their drug purchases. It is a lucrative business that has made a few groups of people richer while billions of others suffer. Heroine is the popular drug among drug users in Malaysia, where it is normally injected through the veins at some parts of the body. There is danger of transmitting HIV virus when the addicts share their needles. SAHABAT in Kota Bharu, Kelantan is a NGO that conducts Needle and Syringe Exchange Programme (NSEP), to stop the spreading of the virus. The paper intends to highlight that drug trafﬁcking not only lead to drug abuse, but it has caused individuals and public at large to bear the consequences cost. The direct consequences costs of drug trafﬁcking are larger compared to the indirect costs.